2015
DOI: 10.1155/2015/293868
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Equations to Predict Positive Airway Pressures for Obstructive Sleep Apnea: A Systematic Review

Abstract: Objective. To systematically review the international literature for mathematical equations used to predict effective pressures for positive airway pressure (PAP) devices. Methods. Google Scholar, PubMed, Scopus, Embase, Web of Science, CINAHL, and The Cochrane Library were searched through June 27, 2015. The PRISMA statement was followed. There was no language limitation. Results. 709 articles were screened, fifty were downloaded, and twenty-six studies presented equations that met the inclusion and exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 68 publications
1
34
0
20
Order By: Relevance
“…The most recent Cochrane reviews however found no statistically significant difference between the various available appliances (28,29). Research continues in predicting CPAP pressure requirements and many parameters have been suggested including BMI, mean oxygen saturation, mean respiratory disturbance index, gender, depression and mask leak-with the strongest mathematical weighting for BMI and mean oxygen saturation (30)(31)(32)(33).…”
Section: Application Modifications and Patient Interventionsmentioning
confidence: 99%
“…The most recent Cochrane reviews however found no statistically significant difference between the various available appliances (28,29). Research continues in predicting CPAP pressure requirements and many parameters have been suggested including BMI, mean oxygen saturation, mean respiratory disturbance index, gender, depression and mask leak-with the strongest mathematical weighting for BMI and mean oxygen saturation (30)(31)(32)(33).…”
Section: Application Modifications and Patient Interventionsmentioning
confidence: 99%
“…Our results were in concordance with more severe OSA and lower SaO 2 during NREM sleep. Camacho et al in their systematic review of 26 studies on mathematical equations of CPAP prediction, reported BMI and mean oxygen saturation as the most heavily weighted variables along with BMI, AHI, and neck circumference as the most frequently used variables (Camacho et al, 2015). The likelihood of changing from CPAP to BiPAP was almost doubled by higher BMI and neck circumference in our study population.…”
Section: Discussionmentioning
confidence: 52%
“…Many formulas derived from clinical and para-clinical variables have been developed to predict the optimal PAP. Oxygen desaturation, Apnea Hypopnea Index, and neck circumference are considered to be the main predictive factors for the prediction of CPAP pressure in the body of related literature (Abdel Wahab & Ahmed, 2017;Camacho, Riaz, Tahoori, Certal, & Kushida, 2015;Ebben, Narizhnaya, & Krieger, 2017;Noseda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study of 358 snoring patients also found that NP narrowing, UAL, and MPH seem to play important physiopathogenic roles in OSA [6]. Some studies have reported that any obstruction of the upper airway would have an effect on CPAP titration level by interfering with the airflow [10][11][12], with a consequential impact on CPAP compliance.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research evaluating the possible influential factors in CPAP titration, aimed at lowering economic costs and significantly increasing the tolerance of CPAP therapy, have produced varying results [10,13,14]. A systematic review by Camacho et al [10] showed that BMI and ODI weighed most heavily in the equation that predicted the CPAP titration level. Bosi et al [11] reported that PSG variables and anthropometric parameters had no significant independent predictive value for CPAP titration, with the exception of BMI.…”
Section: Discussionmentioning
confidence: 99%